PENEGAKAN HUKUM TERHADAP TINDAK PIDANA PEMBAKARAN HUTAN (Studi Kasus Putusan Nomor: 74/Pid.Sus/2015/PN.KAG) - WICAKSONO, BUDI (Dinamika Hukum, 2018)
Pollution and environmental damage as in the case of environmental destruction burning Forest Area Conserfation/Forest Moratorium PT. Bumi Mekar Hijau (BMH) Simpang Tiga District Simpang Tiga Village, Tulung Selapan Subdistrict, Ogan Komering Ilir District, has had an impact on human life, such as global warming, flash floods, forest fires, landslides that cause both human and noneconomic resources of society, social and public facilities. Besides causing epidemics of dengue fever, muntaber, lungs and diarrhea and others. Based on this, the author wants to review through environmental crime. This study aims to examine law enforcement against criminal acts of forest burning and examine more appropriate criminal acts in Decision Number: 74/Pid.Sus/2015/PN.KAG. This study uses normative juridical type, the nature of the research is descriptive. Data source used secondary data. Technique of collecting data by conducting library research and document study on Decision Number: 74/Pid.Sus/ 2015/ PN.KAG. Analyze data by collecting data which then connected with existing problems and arranged in a systematic and logical. The results showed that law enforcement against defendant I. Kardomo Als Domo Bin Usup and defendant II. Ali Usman Bin Named for his actions which caused the destruction of the environment in the area of Conservation Forest / Moratorium Forest (protected forest) and Simpang Tiga Village Conservation Forest Simpang Tiga Village, Tulung Selapan Subdistrict, Ogan Komering Ilir Regency, namely :) were sentenced to imprisonment respectively for a period of 1 (one) year and a fine of Rp.250,000,000 (two hundred and fifty million rupiahs) provided that a fine is not paid is replaced with imprisonment for 3 (three) months. Based on the testimony of witnesses, evidence of letters and statements of the defendants and the existence of material evidence, the fact that the burning of land carried out by the defendants has caused a fire of 6100 hectares of land and caused the wood and grass trees on the land to burn up and cause smoke, resulting in pollution and/or destruction of the environment and existing evidence in the hearing, the appropriate criminal act in decision No. 74/Pid.Sus/2015/PN.KAG is a crime act of burning land/ forest. Keywords: Law enforcement, and burning Forest.